(3QSGdI GdCfhGQs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3eMeO Hf YHO GdhgGH Hf CMeO Hf eMeO Hf YHO GdYRjR Hf GdMSjf Hf YHO Gddg GdMHGH GdSYOi s)
(3ChdgG (B:s
(3GdMeO ddg hGgH GdYbd heHOYg hfGUH Gdfbd heTQYg CLHJ SDGdc CjgG Gdehdi GdcQje hGdUai GdMeje ai cjajI GdTchc Edi QH GdYRh JYGdi hGdhUhd Edi MVQJg hGdQLhY Hg ef YfOg Edi Ndbg s
(3BNQgG (B:s
(3hgj ETGQg ajfG adGjRGd GdYGde eJYWTkG OGFekG GHOkG aGdehGgH jJYdb Hg OGFekG GHOkG adeKd gPG adjYed GdYGedhf hai gPG adjJfGaS GdeJfGaShf hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B40s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B849s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs